2014
DOI: 10.1371/journal.pone.0091682
|View full text |Cite
|
Sign up to set email alerts
|

Variable Virulence Factors in Burkholderia pseudomallei (Melioidosis) Associated with Human Disease

Abstract: Burkholderia pseudomallei is a Gram-negative environmental bacterium that causes melioidosis, a potentially life-threatening infectious disease affecting mammals, including humans. Melioidosis symptoms are both protean and diverse, ranging from mild, localized skin infections to more severe and often fatal presentations including pneumonia, septic shock with multiple internal abscesses and occasionally neurological involvement. Several ubiquitous virulence determinants in B. pseudomallei have already been disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
156
5
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(191 citation statements)
references
References 36 publications
13
156
5
2
Order By: Relevance
“…Similarly, spread via the trigeminal nerve fascicles could be influenced by BimA-facilitated infection of the olfactory mucosa in order to gain access to the trigeminal nerve endings; alternatively BimA-mediated uptake by Schwann cells and cell-to-cell spread may facilitate entry to the nerve fascicle. Significantly, our data showing that absence of BimA results in reduced olfactory bulb infection are in accord with clinical data strongly suggesting a link between BimA function and neurological melioidosis (36). There are two alleles of bimA extant in B. pseudomallei: one, bimA Bp , typical of the majority of B. pseudomallei isolates, and another, bimA Bm , resembling that from Burkholderia mallei and present in 12.1% of Australian isolates (37).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, spread via the trigeminal nerve fascicles could be influenced by BimA-facilitated infection of the olfactory mucosa in order to gain access to the trigeminal nerve endings; alternatively BimA-mediated uptake by Schwann cells and cell-to-cell spread may facilitate entry to the nerve fascicle. Significantly, our data showing that absence of BimA results in reduced olfactory bulb infection are in accord with clinical data strongly suggesting a link between BimA function and neurological melioidosis (36). There are two alleles of bimA extant in B. pseudomallei: one, bimA Bp , typical of the majority of B. pseudomallei isolates, and another, bimA Bm , resembling that from Burkholderia mallei and present in 12.1% of Australian isolates (37).…”
Section: Discussionsupporting
confidence: 87%
“…The genomic data were also used to determine the distribution of the mutually exclusive BTFC/YLF gene clusters (39) in the 455 B. pseudomallei strains in silico. The BTFC cluster is common in Australian strains (between 79 and 88% in other published studies [39,40] and 65% in our data set), whereas Asian strains almost exclusively carry YLF, as evidenced by 30/31 (97%) of the Asian genomes in our data set containing YLF (see Table S2 in the supplemental material). The ST-562 strains all harbored YLF, adding further weight to the hypothesis of an Asian origin for these strains.…”
Section: Mlst Analyses Suggest That St-562 Is Asian In Originsupporting
confidence: 59%
“…The detection of ST-562 in northern Australian melioidosis cases is of concern for several reasons, not least of which is the higher melioidosis mortality rate in Asia (2), which may in part be attributable to heightened infectivity or virulence potential of Asian strains (40). Of the 455 melioidosis cases identified between October 1989 and August 2014 that have been epidemiologically linked to the Darwin region, 28 were caused by ST-562.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4B to D demonstrate B. pseudomallei localized within the branches of the trigeminal nerve. As noted above, clinical evidence points to a role for BimA, and hence actin-mediated motility, in neurological melioidosis (229); assuming inhalational acquisition to be associ-ated with such cases, it remains to be determined where in the olfactory/trigeminal pathways such motility is utilized.…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriamentioning
confidence: 99%
“…To our knowledge, the ability of B. pseudomallei to directly invade HBMECs has not been investigated, but it would be reasonable to hypothesize that the intracellular lifestyle of B. pseudomallei may contribute to the pathogenesis of CNS invasion. Interestingly, a recent study investigated the variable virulence factors of B. pseudomallei associated with melioidosis in Australia and reported that B. pseudomallei strains harboring a bimA allele that shares 95% homology with B. mallei bimA (bimA Bm ) (228) were significantly associated with neurological melioidosis (229). Patients that were infected with B. pseudomallei harboring the bimA Bm allele were found to be 14 times more likely to present with neurological involvement than patients infected with strains harboring the B. pseudomallei bimA variant (bimA Bp ) (229), indicating a role for actin-mediated motility in either transgression of the BBB/BCSFB or transit to the brain via the olfactory or trigeminal nerve pathways (see below).…”
Section: Bacterial Mechanisms Of Brain Invasionmentioning
confidence: 99%